Nicht Nachahmung, sondern Nachfolge: Kants Reflexionen zum ethischen Exempel - Witschen, Dieter (Zeitschrift für katholische Theologie, 2008)
Which role does the moral example play in Kant's ethics? Does the example of the moral person for Kant have a function in normative ethics? Or does it have a role to play for moral motivation, or for moral education? And what can be learned from Kant for moral theology? The article reflects on these questions paying special attention to Kant's distinction between following Jesus and imitating him.